2005
DOI: 10.1111/j.1365-2141.2005.05631.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the interleukin‐2 receptor antagonist basiliximab in steroid‐refractory acute graft‐versus‐host disease

Abstract: Acute graft-versus-host disease (aGVHD) occurs in up to 80% of patients who undergo allogeneic stem cell transplantation (SCT) and contributes significantly to transplant-related mortality (TRM). We conducted a prospective phase II trial to assess the efficacy and feasibility of treating steroid-refractory aGVHD with basiliximab, a chimaeric monoclonal antibody directed against the alpha chain of the interleukin-2 (IL-2) receptor. Basiliximab was administered intravenously at a dose of 20 mg on days 1 and 4. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
5
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 49 publications
9
64
5
1
Order By: Relevance
“…16 In previous studies, the chimeric IL-2R antibodies binding with high affinity to the a-chain of the IL-2R, daclizumab, or basiliximab were given as a single second-line agent to patients with SR-aGVHD. CR was achieved in 17%-37% of patients and 6-mo OS was poor, at only 28-55%, 10, 17, 18 while 5-y OS was 20%. 11 On the other hand, earlier animal models had suggested that TNF-a played a major role in aGVHD of gastrointestinal (GI) tract and skin.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…16 In previous studies, the chimeric IL-2R antibodies binding with high affinity to the a-chain of the IL-2R, daclizumab, or basiliximab were given as a single second-line agent to patients with SR-aGVHD. CR was achieved in 17%-37% of patients and 6-mo OS was poor, at only 28-55%, 10, 17, 18 while 5-y OS was 20%. 11 On the other hand, earlier animal models had suggested that TNF-a played a major role in aGVHD of gastrointestinal (GI) tract and skin.…”
Section: Discussionmentioning
confidence: 94%
“…Acute GVHD involved skin in 54 patients, gut in 59 patients, and liver in 42 patients. The median number of infusions of basiliximab was 4 (range [2][3][4][5][6][7][8][9][10][11], and the median number of etanercept was 9 (range 2-12). At day 28 after the initiation of treatment with the combination of basiliximab and etanercept, the overall response rate (ORR) (CRCPR) to second-line treatment was 90.8% (59/65) including 49 CRs (75.4%).…”
Section: Gvhd Responsementioning
confidence: 99%
See 1 more Smart Citation
“…This was thought to be a result of depletion of Tregs and their regulatory role in aGVHD. Other IL2 antibodies are in clinical trials as well [94,95]. Basiliximab is a shorter acting IL2 receptor antibody.…”
Section: Anti-interleukin 2 Receptor Antibodiesmentioning
confidence: 99%
“…Basiliximab is a shorter acting IL2 receptor antibody. It has been associated with modest responses when used in treatment of aGVHD [95].…”
Section: Anti-interleukin 2 Receptor Antibodiesmentioning
confidence: 99%